2020
DOI: 10.21203/rs.3.rs-17902/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simethicone administration improves efficacy and efficiency of esophagogastroduodenoscopy

Abstract: Background: Esophagogastroduodenoscopy is very useful in diagnosing and treating upper gastrointestinal mucosal disorders, but too much foam and water in stomach decrease its diagnostic efficiency. Simethicone administration can help remove excessive foam. Aims: To determine the optimal simethicone administration strategies in a comparative randomized controlled clinical trial.Methods: Adult outpatients with indications for esophagogastroduodenoscopy were enrolled and randomly divided into Group 1 (simethicone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 13 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…9,12,13 Shengjing recipe also improved grade A and A+B sperms, and to a greater extent than in the Xuanju capsule group. These results are supported by Sun et al, 11 who showed 16 showed that Shengjing recipe could improve sperm density and motility, and increase the pregnancy rate. Similar results were observed by Song et al, 17 Guo et al, 18 Zhang et al, 19 and Chen et al 20 These effects are also supported by animal studies that shed some light on the mechanisms of Shengjing recipe.…”
supporting
confidence: 62%
See 4 more Smart Citations
“…9,12,13 Shengjing recipe also improved grade A and A+B sperms, and to a greater extent than in the Xuanju capsule group. These results are supported by Sun et al, 11 who showed 16 showed that Shengjing recipe could improve sperm density and motility, and increase the pregnancy rate. Similar results were observed by Song et al, 17 Guo et al, 18 Zhang et al, 19 and Chen et al 20 These effects are also supported by animal studies that shed some light on the mechanisms of Shengjing recipe.…”
supporting
confidence: 62%
“…The above drugs were used together to enhance the effect of sperm production. 11 In the present study, Xuanju capsule, a classical TCM for male infertility, was used as positive control and showed improvements in grade A and A+B sperms. 9,12,13 Shengjing recipe also improved grade A and A+B sperms, and to a greater extent than in the Xuanju capsule group.…”
mentioning
confidence: 76%
See 3 more Smart Citations